2017
DOI: 10.29244/jitkt.v9i2.19257
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH AND PROTEIN CONTENT OF Ulva prolifera MAINTAINED AT DIFFERENT FLOW RATES IN INTEGRATED AQUACULTURE SYSTEM

Abstract: Efforts to reduce the impact of waste improvement on degradation of water quality can be transferred by utilization of inorganic waste as a source of seaweed nutrition. This study aimed to determine the growth and protein content of Ulva prolifera maintained at different flow rates in integrated aquaculture system. 9 Yellowtail stocked with 5.095 g with an average weight of 566.11±81.51 g were kept in 540 L tank for 24 days, by water flowing at the rate of 10 L min-1. Water from the fish tank was distributed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…generally showed high biofiltering efficiencies. In accordance, previous studies have shown that macroalgae from genus Ulva can efficiently remediate aquaculture effluents [5,32,39,46,49,55,56]. Nutrient removal rates within the same order as those reported in literature were attained in this work and, generally, NRE showed a tendency to increase in autumn for nitrogen compounds (LU2 and AQU2) and in spring for phosphorous compounds (AQUA1).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…generally showed high biofiltering efficiencies. In accordance, previous studies have shown that macroalgae from genus Ulva can efficiently remediate aquaculture effluents [5,32,39,46,49,55,56]. Nutrient removal rates within the same order as those reported in literature were attained in this work and, generally, NRE showed a tendency to increase in autumn for nitrogen compounds (LU2 and AQU2) and in spring for phosphorous compounds (AQUA1).…”
Section: Discussionsupporting
confidence: 91%
“…In IMTA systems, Msuya et al and Al-Hafedh et al reported similar SGR values [40,44,45], although lower biomass yields were achieved in one's study. On the other hand, higher SGR values (>18% day −1 ) have been reported in previous works [5,39,46] which used continuous effluent flow.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The cultivation of macroalgae may also be done in a variety of systems from raceways to settling ponds. Water flow and aeration may be necessary to promote the renewal of the boundary layer between algae and water surfaces, in order to favour the diffusion of the nutrient into the algal biomass (Diamahesa, Masumoto, Jusadi, & Setiawati, 2017). Relying on nutrient concentration and water flow, which can range from one to sixteen water exchanges (per day), it is possible to enhance nutrient uptake and growth (Neori et al, 2003).…”
Section: Macroalg Ae Produc Tionmentioning
confidence: 99%
“…Relying on nutrient concentration and water flow, which can range from one to sixteen water exchanges (per day), it is possible to enhance nutrient uptake and growth (Neori et al, 2003). If the water flow is low, nutrients will become limiting, biomass production will decrease, but the nutrient uptake efficiency will increase (Diamahesa et al, 2017). This may be an alternative, whenever sample space for extensive systems is available.…”
Section: Macroalg Ae Produc Tionmentioning
confidence: 99%